2019
DOI: 10.3390/cancers11050605
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Non-Coding RNAs in Lung Cancer Tumorigenesis

Abstract: Lung cancer is the most prevalent and deadliest cancer worldwide. A significant part of lung cancer studies is dedicated to the expression alterations of non-coding RNAs. The non-coding RNAs are transcripts that cannot be translated into proteins. While the study of microRNAs and siRNAs in lung cancer received a lot of attention over the last decade, highly efficient therapeutic option or the diagnostic methods based on non-coding RNAs are still lacking. Because of this, it is of utmost importance to direct fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 115 publications
1
76
0
Order By: Relevance
“…CircRNAs play pivotal roles in the tumorigenesis of lung cancer . By detecting the expression of circRNA in patient tissues and cell lines, we found that circCDR1as expression was enhanced in NSCLC, indicating that high expression of circCDR1as could contribute to the malignancy of NSCLC.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…CircRNAs play pivotal roles in the tumorigenesis of lung cancer . By detecting the expression of circRNA in patient tissues and cell lines, we found that circCDR1as expression was enhanced in NSCLC, indicating that high expression of circCDR1as could contribute to the malignancy of NSCLC.…”
Section: Discussionmentioning
confidence: 87%
“…Among these types, circular RNA (circRNA) consists of a continuous closed loop . Several circRNAs have been reported to be aberrantly expressed and associated with the tumorigenesis of lung cancer . Furthermore, emerging evidence suggests that several circRNAs might contribute to the progression of NSCLC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are transcripts that lack the 5′end cap and a 3′ end poly(A) tail, forming a covalent closed loop [74]. e mechanism of circRNA mainly includes interactions with chromatin histones, binding to RNA polymerase, capturing proteins from its original mRNA, encoding exons and sponge miRNAs, capturing transcription factors in the cytoplasm, and preventing gene transcription [75,76]. With the development of high-throughput sequencing technology, an increasing number of differentially expressed circRNAs have been discovered that are involved in the development of lung cancer.…”
Section: Ncrnas In Lungmentioning
confidence: 99%
“…Non‐coding RNAs make up most of the transcriptome, while protein‐coding RNAs only account for 3% of the genome; the remaining 97% is composed of “dark matter” of transcripts with molecular functions 3 . It has been proven that the genome “dark matter” can be transcribed into various RNA species, most of which do not encode proteins, namely, ncRNAs, but exert significant functions mainly responsible for phenotypic regulation 4 .…”
Section: Introductionmentioning
confidence: 99%